Factors Associated with Frailty: A Population Based-study among the Rural Elderly Community - Morala-Dimaandal, Dwellers Dorothy; Shiomi, Taizo; Maruyama, Hitoshi (JPAIR Multidisciplinary Research, 2008)
The aims of this study were two-fold: to identify factors associated with frailty and to determine their ability to predict frailty among elderly community-dwellers in rural areas. The study involved 100 randomly selected elderly individuals aged 65 to 80 years, who completed the Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), Physical Performance Test (PPT), and questionnaires. Logistic regression models revealed that cognitive function, as measured by the MMSE, had the strongest association with frailty. Additionally, education, age, and scores on the GDS were significant indicators of a lower risk of frailty. The interrelated nature of cognitive function and functional status highlights the importance of cognitive impairment on frailty, with cognitive function having a stronger association with physical frailty than any other measured variable. This suggests that incorporating a treatment regimen that stimulates cognitive function could enhance functional levels or prevent functional decline more effectively than exercise interventions alone.
Keywords: frailty; cognitive function; functional status; elderly